2014
DOI: 10.1155/2014/806082
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, Phytotherapeutical and Pharmacological Study of Momordica dioica

Abstract: Momordica dioica is a perennial, dioecious, cucurbitaceous climbing creeper (commonly known as kakrol, spiny gourd or teasle gourd). It is native to Asia with extensive distribution in India and Bangladesh. It is used not only as preventive and curative agent for various diseases but also as vegetable with a significant nutritional value over thousands of years. This review aims to take an attempt to evaluate the phytochemical, ethnobotanical, phytotherapeutical and pharmacological properties of kakrol accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…Similarly methanol and aqueous extract of its fruit pulp have neuroprotective activities in-vivo 45 . Claimed that Phenolic, flavonoids in Phaseolus vulgaris are helpful in preventing depression as well as having the ability to remove ROS 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly methanol and aqueous extract of its fruit pulp have neuroprotective activities in-vivo 45 . Claimed that Phenolic, flavonoids in Phaseolus vulgaris are helpful in preventing depression as well as having the ability to remove ROS 46 .…”
Section: Resultsmentioning
confidence: 99%
“…The extracts of Momordica dioica and Caesalpinia bonduc were subjected to preliminary phytochemical analysis [14], testing for the detection of different chemical groups of compounds. Air-dried and powdered plant materials were screened for the presence of, total phenols and flavonoids.…”
Section: Preliminary Phytochemical Analysismentioning
confidence: 99%
“…Phenolic compounds are plant secondary metabolites produced either from phenylalanine or from its precursor shikimic acid [14]. The phenolic compounds are capable of the direct chain breaking antioxidant action by free radical scavenging.…”
Section: Determination Of Total Phenolic Contentmentioning
confidence: 99%
“…The M. dioica has several medicinal uses (Talukdar and Hossain 2014). Dried fruit powder produces a powerful errhine effect when applied into the nostrils.…”
Section: Momordica Speciesmentioning
confidence: 99%
“…The tubers of the teasle gourd act as antihelminthic, spermicidal, and antifertility as well as abortifacient agent. Beside these, it has antioxidant, analgesic, nephroprotective, neuroprotective, antiallergic, antiulcer, anticancer, antimicrobial, antimalarial, hepatoprotective, antihepatotoxic, antiedemic and insecticidal properties (Talukdar and Hossain 2014). Narasimhan et al (2005) showed antifeedant activity of M. dioica against Spodoptera litura and the seed oil of M. dioica could be used as grain protectant against Callosobruchus chinensis (Mishra et al 2006).…”
Section: Momordica Speciesmentioning
confidence: 99%